Systemic allergic dermatitis caused by Apiaceae root vegetables. (19th September 2013) - Paulsen, Evy; Petersen, Thomas H.; Fretté, Xavier C.; Andersen, Klaus E.; Christensen, Lars P.
Summary Background Immediate hypersensitivity reactions to root vegetables of the Umbelliferae plant family (Apiaceae) is well known. Delayed‐type hypersensitivity is rarely reported. Objective To report the first case of systemic contact dermatitis caused by root vegetables and some chemical implications. Materials and methods Prick and patch testing were performed with fresh vegetables and selected allergens, and this was followed by high‐performance liquid chromatography–mass spectrometry (MS)/MS analysis of the falcarinol syringe. Results The patient was contact‐sensitive to celeriac, parsnip, and carrot, but tested negative to falcarinol. Subsequent analysis showed that the syringe contained falcarinol. Conclusion The non‐occupational sensitization resulting from both direct and systemic contact with Apiaceae root vegetables was apparently not caused by falcarinol.